Simulation and experimental investigation of single CVD micro-edge diamond abrasive grain grinding - Dongdong Liu; Haojie Zhu; Rui Shen; Fanghong Sun (Journal of Materials Research and Technology)
Precision grinding relies on the micro-cutting effect of abrasive grain micro-edges during material processing. However, there currently lacks an effective method to generate numerous sharp micro-cutting edges on single-crystal diamond abrasive grains. In this paper, the micro-edge diamond abrasive grains fabricated by the hot filament chemical vapor deposition (HFCVD) method grow numerous pyramidal polycrystalline structures. The SiC ceramics grinding simulation is accomplished to demonstrate the grinding and material removal mechanism of CVD micro-edge diamond abrasive grains applying finite element method (FEM) based on the established three-dimensional (3D) numerical model. Furthermore, grinding experiments on silicon carbide (SiC) ceramics are conducted to investigate micro-edge grinding performance and grinding mechanism employing novel single-grain CVD micro-edge diamond grinding tools compared with conventional diamond grinding tools. The micro-edge ground surface produces finer grinding marks instead of crushed chips, and observed subsurface forms slip bands without cracks under the decreased grinding force, which changes the material removal mode from brittle fracture to plastic deformation removal. The grinding mechanism of micro-edge diamond abrasive grains is to increase numerous pyramidal micro-edges contact with the grinding workpiece. The unit average pressure of the workpiece subjected to the single micro-edge decreases due to the lower grinding force under the same grinding conditions. The ground material is rubbed, ploughed and cut by the micro-edges within the plastic limit, which does not produce brittle fracture.